THE EFFECT OF FREE CASH FLOW, FINANCIAL DISTRESS, AND CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE ON EARNING MANAGEMENT IN INFRASTRUCTURE COMPANIES - Putri Ramadhani; Harti Budi Yanti (ZILLZELL MEDIA PRIMA, 2024)
This study aims to analyze the influence of free cash flow, financial distress and corporate social responsibility disclosure on earning management. This study uses infrastructure companies in 2019-2023 with samples obtained from 47 companies multiplied by 5 years so that 235 observations are obtained. The results of the study prove that cash flow and CSR disclosure have a negative and significant effect on earning management. Meanwhile, financial distress has no effect on earning management. The implication of the research in this study is that managers must consider the long-term impact of doing earning management, especially in the context of the company's financial condition and managers' involvement in CSR practices. While profit manipulation may provide short-term profits, it can damage the company's reputation and sustainability in the future. Furthermore, CSR disclosure can increase company transparency and this can help create greater trust with external stakeholders.